PERAHU LANCANG KUNING KEARIFAN LOKAL MASYARAKAT MELAYU BINTAN KEPULAUAN RIAU - Samin, Rumzi; Khodijah, Khodijah (Jurnal Ilmu Administrasi Negara (JUAN), 2018)
The Lancang Kuning boat research that is oriented to Identification, documentation, Inventory, data and local wisdom and the use of technology that has local nuances on a provincial scale that is more maritime oriented. Therefore this research is in line with the RIP Lancang Kuning local wisdom of the Malay people of Bintan Riau Islands". This research was conducted with the aim of inventorying local wisdom, its influence on society, problems that arise in development and how to determine strategies for their existence. The research methodology was carried out by collecting both primary and secondary data both quantitative and qualitative from stakeholders, through discussions, in-depth interviews and questions. This study will explore three types of Malay heritage that were used in trade activities and maritime activities in the past; namely the type of large ship for exploration in the ocean and between continents, a type of simple ship for exploration between ports in Alam Melayu and types of boats or small boats for beach and river activities. The Lancang Kuning boat is a traditional boat in Indonesia, in some areas the form of traditional boats still exists today but the Lancang Kuning boat is not found in the environment of the Riau Islands Malay community. For that, it is necessary to explore and deepen seriously looking for historical